2019
DOI: 10.1038/s41430-019-0485-y
|View full text |Cite
|
Sign up to set email alerts
|

A multi-center survey on hospital malnutrition and cachexia in Slovenia

Abstract: Background Malnutrition has become a prevalent condition, with European and international studies reporting rates of approximately 25-40% in hospitals. We set out to perform a multi-center cross-sectional study to assess malnutrition rates in Slovenian hospitals and to convert the findings into a mobile application suitable for use by nurses and staff at the bedside. In addition, we examined the association of the results of this mobile application with parameters for body composition measured by bioimpedance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…The PhA can serve as a sensitive indicator for monitoring the nutritional status of CD patients. According to several studies, the PhA is related to the nutritional status of patients in other diseases, with a lower PhA indicating poorer nutritional status [ 7 , 45 , 46 , 47 , 48 ]. These findings are similar to those in our study, which showed a positive correlation between PhA and nutritional status [ 14 , 15 , 49 ]; PhA < 6.11° and < 5.55° could be used as cut-off points for diagnosing malnutrition in males and females, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PhA can serve as a sensitive indicator for monitoring the nutritional status of CD patients. According to several studies, the PhA is related to the nutritional status of patients in other diseases, with a lower PhA indicating poorer nutritional status [ 7 , 45 , 46 , 47 , 48 ]. These findings are similar to those in our study, which showed a positive correlation between PhA and nutritional status [ 14 , 15 , 49 ]; PhA < 6.11° and < 5.55° could be used as cut-off points for diagnosing malnutrition in males and females, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Considered to be a new promising nutritional status assessment method, bioelectrical impedance analysis (BIA) is a noninvasive tool that can be used to assess body composition based on the relationship between total body impedance and total body water. The phase angle (PhA), which represents an indicator of cellular health and membrane integrity, is a variable that is easily calculated using resistance (R) and reactance (Xc) values determined by BIA [ 7 ]. Recently, several studies have indicated that the BIA-derived PhA, a superior prognostic marker, can be considered as a screening tool for the identification of at-risk patients with impaired nutritional and functional status [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estudios han encontrado que la edad del paciente es un factor que puede influenciar en el grado de desnutrición una vez que estos han sido hospitalizados (Behiry & Salem, 2019;González-Franco et al, 2020;Lovera Montilla & Cáceres Villota, 2023). Mientras más edad presente el paciente, el riesgo de desnutrición aumenta y por tanto también aumenta el riesgo de fallecer (Bhirommuang et al, 2019;Boaz & Kaufman-Shriqui, 2023;Koroušić Seljak et al, 2020;Pereira et al, 2021;Ting et al, 2019) sobre todo con afectaciones como el COVID 19 (Velázquez Alva et al, 2021) y enfermedades renales (Sánchez-Tocino et al, 2022). En el caso de los pacientes oncológicos hospitalizados, no hubo diferencias respecto a las edades, sin embargo presentan las tasas más elevadas de desnutrición hospitalaria (Chimera-Khombe et al, 2022).…”
Section: Resultsunclassified
“…Higher levels of inflammation with higher ECW/TBW may indicate that patients have a great nutritional risk and a worse prognosis. Researchers had found that the malnutrition was associated with greater ratio of ECW [ 49 , 50 ]. We found higher ECW/TBW showed worse prognosis in patients with malnutrition.…”
Section: Discussionmentioning
confidence: 99%